Magic and Monsters: Collaborating with Googlei in Literacy Practices - Ott, Mary; Kassen, Jenny; Hibbert, Kathryn (Language and Literacy / Langue et littératie, 2022)
Collaboration is one of the defining features of work and learning in the 21st century. Yet despite the proliferation of Google apps and devices for collaboration across North American school systems, the scope of research on student collaboration using Google technologies in elementary school settings is limited. This paper presents findings from two cases in grade five classrooms where teachers were experimenting with using Google Docs and Chromebooks in their literacy programs. Drawing on a conceptual framework of sociomaterial, complexity, and affect theories, the study offers insights for teachers to understand the complexities of collaboration with these technologies, and pedagogical implications for working with the magic and monsters of unintended effects in collaborative literacy practices.